Secondary School Parents' Opinions On Digital Parenting - Pullu, Emine Kübra; Gömleksiz, Mehmet Nuri (Salim DURUKOĞLU, 2023)
The purpose of this research is to determine the views of secondary school students' parents on digital parenting. Phenomenology design, one of the qualitative research methods, was used in the research. The study group of the study, which was determined by the easily accessible situation sampling, included 20 parents whose children were studying at the second level of primary education in the center of Elazig. The data of the study were collected with a semi-structured interview form consisting of 10 questions developed by the researchers. The data obtained from the interviews with their parents were analyzed according to the content analysis method. As a result of the research, 7 themes emerged regarding parents' views on digital parenting. These themes are: 'Aims and frequency of use of digital technologies', 'Children and video watching applications', 'Children and digital games', 'Children and online shopping', 'Children and social media applications', 'Educational use of digital technologies' and 'Children and safe use of digital technologies'.

Bu araştırmanın amacı, ortaokul öğrenci velilerinin dijital ebeveynliğe yönelik görüşlerinin belirlenmesidir. Araştırmada nitel araştırma yöntemlerinden olgubilim deseni kullanılmıştır. Kolay ulaşılabilir durum örneklemesi ile belirlenen araştırmanın çalışma grubunda çocukları Elazığ merkezde ilköğretim ikinci kademede öğrenim gören 20 ebeveyn yer almaktadır. Araştırmanın verileri araştırmacılar tarafında geliştirilen ve 10 sorudan oluşan yarı yapılandırılmış bir görüşme formu ile toplanmıştır. Ebeveynleri ile yapılan görüşmelerden elde edilen veriler içerik analizi yöntemine göre çözümlenmiştir. Araştırma sonucunda velilerin dijital ebeveynliğe görüşlerine yönelik 7 tema ortaya çıkmıştır. Bu temalar: ‘Dijital teknolojilerin kullanım amaçları ve sıklıkları’, ‘Çocuklar ve video izleme uygulamaları, ‘Çocuklar ve dijital oyunlar’, ‘Çocuklar ve online alışveriş’, ‘Çocuklar ve sosyal medya uygulamaları’, ‘Dijital teknolojilerin eğitsel kullanımı’ ve ‘Çocuklar ve dijital teknolojilerin güvenli kullanımı’ şeklindedir.
Ortaokul Öğrenci Velilerinin Dijital Ebeveynliğe İlişkin Görüşleri
Keywords: Turkish Education; Türkçe Eğitimi